INJURIES TO THE PRIMARY TEETH AND SOFT TISSUES IN CHILDREN IN NIS, SERBIA - Igić, Ana; Stojkovic, Branislava; Mitic, Aleksandar; Acovic, Aleksandar; Todorovic, Kosta; Todorovic, Ana; Sokolovic, Dusan; Igic, Marija (Acta medicae Medianae, 2021)
The aim of this study was to analyze injuries to the primary teeth and adjacent soft tissues in relation to the gender and age of injured children, type of injury, place, and mechanism of injury. The study enrolled 115 children (71 boys and 44 girls) managed at the Dentistry Clinic, Faculty of Medicine University of Niš, in the period 2009-2019. The information about the type of injury, place, and mechanism of injury were obtained from the medical records of the patients aged 1-5 years. Our analysis established that there were statistically significantly (p
Keywords: primary teeth; injuries; subluxation; laceration